2016
DOI: 10.5603/kp.a2016.0008
|View full text |Cite
|
Sign up to set email alerts
|

Interarm systolic blood pressure difference is associated with myocardial injury after noncardiac surgery

Abstract: A b s t r a c tBackground: Myocardial injury after non-cardiac surgery (MINS) is closely related to increased cardiovascular mortality.Aim: To evaluate the relationship between MINS and interarm systolic blood pressure difference (IASBPD), which has previously been shown to correlate with the frequency of cardiovascular events and arterial arteriosclerotic processes. Methods:This observational, single-centre cohort study included 240 consecutive noncardiac surgery patients aged ≥ 45 years. Simultaneous blood p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Those factors, even despite the older age of patients are risk factors for perioperative complications in hip replacement. It was recently shown that SBP values in the perioperative period are the good predictor of myocardial injury after surgery [13]. While Figure 3.…”
Section: Discussionmentioning
confidence: 93%
“…Those factors, even despite the older age of patients are risk factors for perioperative complications in hip replacement. It was recently shown that SBP values in the perioperative period are the good predictor of myocardial injury after surgery [13]. While Figure 3.…”
Section: Discussionmentioning
confidence: 93%
“…Sequential measurements have a tendency to overestimate difference compared to simultaneous measurements. Recent studies have confirmed that the IASBPD is closely associated with cardiovascular mortality and peripheral arterial disease [ 9 , 10 ]. The relationship between poor outcome and arterial stiffness in cardiovascular diseases has been demonstrated in different patient populations [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The patients were made to sit for 5 minutes, with feet flat on the ground and back supported before BP measurements were taken. Two separate oscillometric blood pressure (BP) monitors with their own cuffs were used randomly, placed at the appropriate location on the arm and measured by the same trained nurse [ 9 ]. BP devices were validated by European Society of Hypertension (Omron HEM-7001-E; Omron Corp., Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations